Perbaikan Sifat Tanah pada Lahan Berpasir Dengan Pemberian Pupuk Kandang dan Pupuk Hayati - Putri Tria Santari; Mirawanty Amin; Ronny Mulyawan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Santari PT, Amin M, mulyawan R. 2021. improvement of Soil Properties on Sandy Soil By Providing Amelliorant and Biofertilizers. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 854-862. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Nutrients N, P, K are nutrients needed by plants in large amounts because these elements affect the growth and production of plants. N, P, K deficiencies are often found, especially in sandy soil types. Sandy soil has a low content of organik matter and nutrients. In sandy soil, the sand fraction content is high so that the nutrients are not easily bound, it is easy to pass water, and the total number of microorganisms is relatively low. The existence of these obstacles makes sandy soils need further management so that they can be used optimally. Ways that can be done to improve and increase the status of soil fertility are by giving manure and biological fertilizers. It is believed that the application of manure and biological fertilizer can improve physical, chemical, and biological properties. The provision of manure and biological fertilizers can increase plant productivity because they can be a stimulant in nutrient availability and improving soil physical properties. Several studies and literature on the application of manure and biological fertilizers on sandy soils have been carried out, either singly or in combination. This paper aims to compile the results of research on the application of manure and types of biological fertilizers applied to sandy soils so that a conclusion can be found that can be recommended by farmers in managing sandy soils.